Occurrence of hypoalbuminemia in cases of rhino-orbito-cererbral mucormycosis and its relationship with the disease severity according to staging, a tertiary care center-based study - Shyamash Mandal; Monoj Mukherjee; Satish Reddy Satty; Souvik Das; Atanu Chandra (Asian Journal of Medical Sciences, 2022)
Background: Mucormycosis is a serious but rare fungal infection with increasing incidence of rhino-orbito-cerebral mucormycosis (ROCM) in the setting of COVID-19. Some studies have shown presence of hypoalbuminemia in cases of mucormycosis, which can affect the prognosis, outcome, and also the drug toxicity in a significant way. A staging of ROCM was proposed and is being used widely based on clinical symptoms and signs, evaluation, and diagnosis. Aims and Objectives: Our objective was to look for any relationship between two factors, occurrence of hypoalbuminemia and severity of ROCM according to staging. Materials and Methods: The study was a hospital-based prospective cross-sectional study done on 41 ROCM patients. All patients of diagnosed ROCM were included by complete enumeration method. Serum albumin of every patient was measured using standard biochemical procedures and patients were divided into groups of normoalbuminemia (Serum albumin level >3.5 gm/dl), mild hypoalbuminemia (Serum albumin level 2.5–3.5 gm/dl), and severe hypoalbuminemia (Serum albumin level <2.5 gm/dl). All the patients were divided into Stage 1, 2, 3, and 4 according to severity of ROCM. Then, the occurrence of hypoalbuminemia was calculated among the patients and correlation between ROCM stages and severity of hypoalbuminemia was measured using standard statistical tools. Results: Among the patients of ROCM, 15% patients did not develop any hypoalbuminemia. About 51% developed mild hypoalbuminemia and 34% developed severe hypoalbuminemia. Maximum number of severe hypoalbuminemia patients were found in the Stage 3 group [total 6 (35%)], but the incidence of the same was maximum in the Stage 4 group (56%). Mild hypoalbuminemia is most common (10) and also most prevalent in the Stage 3 group (59%). Conclusion: We found out that serum albumin level is significantly affected by ROCM severity, that is, more severe the disease, more chance to develop hypoalbuminemia.